Tratamento pós-colheita visando a longevidade floral de gladíolos (Gladiolus x hortulanus) - Cásares Wong, María Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Flowers and ornamental plants potentially have the greatest economic value in horticulture products, and they are the most perishable too. Loss of value in cut flowers is consequence of flower senescence, deterioration caused by pathogens and loss of turgor of products due to negative water balance. Gladiolus or palm-of- Santa-Rita (Gladiolus x hortulanus) is a well-known and appreciated inflorescence, but the short vase life and poor bud opening when harvested immature, limited demand. Although there are postharvest techniques that may help in solving these issues, cut flowers physiology research have been focused on climateric species, in detriment of non-climateric, as the gladiolus. The objective of this study was to evaluate formulations for pulsing and holding solutions to maintain longevity and postharvest quality of gladiolus. In pulsing treatment, gladiolus 'White Goddess' cut inflorescences were treated with sucrose (0, 10, 15 and 20%) for 24 hours. Gladiolus 'White Friendship' cut inflorescences were placed on holding solutions containing different concentrations of germicides (citric acid, 8-hydroxyquinoline - 8HQ, sodium dichloroisocyanurate dehydrate - NaDCC, and polymeric biguanide - PB), sucrose (0, 2, 4 and 8%) and calcium chloride (CaCl2 0.1 and 0.2%). Experimental design was completely randomized with factorial arrangement with three replicates and three inflorescences per repetition. Evaluations were made every three days and according to tested solution, it was considered the following variables: vase life, fresh mass, solution turbidity, respiration, inflorescence postharvest development (showing-color buds, fully-open flowers, wilting flowers and unopened buds), water relations (solution uptake, water loss and water balance), carbohydrate content (soluble and reducing) and membrane stability index. Initial volume (500 mL) of holding solutions was completed on each valuation day. Data were subjected to ...

Flores e plantas ornamentais possuem possivelmente o maior valor econômico dentro dos produtos hortícolas, e também são as mais perecíveis. A perda do valor ornamental das flores depende da senescência das flores, da deterioração causada por patógenos e da perda da turgescência dos produtos devido ao balanço hídrico negativo. O gladíolo ou palma-de-Santa-Rita (Gladiolus x hortulanus) é uma inflorescência muito conhecida e apreciada, porém a curta vida de vaso e as falhas na abertura floral limitam a demanda. Embora existam técnicas póscolheita que podem ajudar na solução destes problemas, os estudos na fisiologia das flores cortadas têm sido focados nas espécies climatéricas, em detrimento das não climatéricas, caso do gladíolo. O objetivo deste trabalho foi avaliar formulações para soluções de “pulsing” e de manutenção na longevidade e qualidade póscolheita do gladíolo. No tratamento de “pulsing”, inflorescências de gladíolo ‘White Goddess’ foram tratadas com soluções de sacarose (0; 10; 15 e 20%) por 24 horas. Inflorescências de gladíolo ‘White Friendship’ foram colocadas em soluções de manutenção formuladas com diferentes concentrações de sacarose (CaCl2 0; 2; 4 e 8%); germicidas (ácido cítrico, 8-hidroxiquinolina-8HQ, dicloroisocianurato de sódio dihidratado-NaDCC e biguanida polimérica - PB), e cloreto de cálcio (0,1 e 0,2%). O delineamento experimental foi inteiramente ao acaso com arranjo fatorial, com três repetições e três inflorescências por repetição. As avaliações foram realizadas a cada três dias e segundo a solução avaliada, consideraram-se as variáveis: vida útil, desenvolvimento pós-colheita da inflorescência (botões mostrando a cor, flores totalmente abertas, flores murchas, botões que permaneceram fechados), massa fresca das inflorescências, turbidez da solução, respiração, relações hídricas (absorção de solução, perda de água ...
Keywords: Flores; Gladiolo; Plantas - Conservação; Calcio; Flores - Qualidade; Sacarose; Pós-colheita; Calcium